Engineering islet for improved performance by optimized reaggregation in alginate gel beads. (26th April 2017) - Li, Na; Sun, Guangwei; Wang, Shujun; Wang, Yu; Xiu, Zhilong; Sun, Dongsheng; Guo, Xin; Zhang, Ying; Ma, Xiaojun
Abstract: After islet isolation, diffusion has become the main mechanism to transport oxygen and nutrients into the core of islets. However, diffusion has limitations, by which nutrients cannot effectively reach the core of large islets and can eventually cause core cell death and islet loss. This problem can be resolved by dispersing islets into single islet cells, but single islet cells do not exhibit insulin release function in in vitro culture. In this study, we intended to establish a new islet engineering approach by forming islet cell clusters to improve islet survival and function. Therefore, alginate gels were used to encapsulate islet cells to form artificial islets after dispersion of islets into single cells. The shape of the islet cell clusters was similar to native islets, and the size of the islet cell clusters was limited to a maximum diameter of 100 μm. By limiting the diameter of this engineered islet cell cluster, cell viability was nearly 100%, a significant improvement over natural islets. Importantly, islet cell clusters express the genes of islets, including Isl‐1, Gcg, and insulin‐1, and insulin secretion ability was maintained in vitro .